Delineating Functional Labour Market Areas with Estimable Classification Stabilities - Benjamin Davies; David C. Maré (Institute of Labor Economics (IZA), 2020)
We describe an unsupervised method for delineating functional labour market areas (LMAs) in national commuting networks. Our method uses the Louvain algorithm, which we extend to support top-down hierarchical LMA classification and estimable classification stabilities. We demonstrate our method using historical Census commuting data from New Zealand.
Keywords: J61; R12; R23; 330; community detection; commuting; functional boundaries; labour market areas; networks